Biomonitoring of occupational exposure to phthalates: a systematic review - Fréry, Nadine (2020)
Introduction: Phthalates, a group of ubiquitous industrial chemicals, have been widely used in occupational settings, mainly as plasticizers in a variety of applications. Occupational exposure to different phthalates has been studied in several occupational settings using human biomonitoring (HBM). Aim: To provide a comprehensive review of the available literature on occupational exposure to phthalates assessed using HBM and to determine future data needs on the topic as part of the HBM4EU project. Methods: A systematic search was carried out in the databases of Pubmed, Scopus, and Web of Science for articles published between 2000 and September 4, 2019, using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A total of 22 studies on the occupational HBM of phthalates were considered suitable for review. Results and discussion: Among the reviewed studies, 19 (86%) focused on DEHP, an old phthalate that is now subject to authorization and planned to be restricted in the EU. Concentrations of MEHHP, one of its metabolites, varied up to 13-fold between studies and across sectors when comparing extreme geometric means, ranging from 11.6 (similar to the general populations) to 151 μg/g creatinine. Only 2 studies focused on newer phthalates such as DiNP and DPHP. Concerning the geographical distribution, 10 studies were performed in Europe (including 6 in Slovakia), 8 in Asia, and 4 in North America, but this distribution is not a good reflection of phthalate production and usage levels worldwide. Most HBM studies were performed in the context of PVC product manufacturing. Future studies should focus on: i) a more uniform approach to sampling timing to facilitate comparisons between studies; ii) newer phthalates, and iii) old phthalates in waste management or recycling. Conclusion: Our findings highlight the lack of recent occupational HBM studies on both old and new phthalate exposure in European countries and the need for a harmonized approach. Considering the important policy actions taken in Europe regarding phthalates, it seems relevant to evaluate the impact of these actions on exposure levels and health risks for workers.